Techno-economic prospects for producing Fischer-Tropsch jet fuel and electricity from lignite and woody biomass with CO2 capture for EOR. (1st December 2020) - Kreutz, Thomas G.; Larson, Eric D.; Elsido, Cristina; Martelli, Emanuele; Greig, Chris; Williams, Robert H.
Highlights: Nine plant configurations for jet fuel made from lignite and woody biomass. Detailed techno-economic assessment study for plants built at commercial-scale. Biomass input fraction is found to significantly affect plant profitability. Energy penalty due to high moisture content (43%) of as-received biomass. High capital and operating costs result in poor economics without a subsidy. Abstract: This study explores the prospective techno-economic performance of facilities that produce low- and net-negative-carbon liquid transportation fuels and electricity with CO2 capture for enhanced oil recovery. The lignite and biomass-to-jet fuel process is based on KBR's TRIG gasifier, Rectisol (for sulfur removal and CO2 capture), fixed-bed low temperature Fischer-Tropsch synthesis of liquid fuels, and Brayton/Rankine combined cycles to convert synthesis/refining off-gases and waste heat to electricity. This work leverages a recent, highly-detailed assessment of a prospective first-of-a-kind (FOAK) demonstration facility to develop highly detailed Aspen Plus process simulations for nine prospective N th -of-a-kind (NOAK) plant equipment configurations. Component-level capital costs from the FOAK study are scaled and adjusted to reflective prospective learning-by-doing to estimate capital costs for the NOAK designs. NOAK plant economic performance is found to be largely insensitive to variations in plant configurations and electricity output fraction, but biomass input fraction significantly affects profitability. Facilities that consume only carbon–neutral biomass, with no lignite co-feed, have significantly net- negative carbon emissions and the most favorable prospective economics when carbon emissions are priced. For these facilities, the crude oil price required for plant economic viability falls rapidly from 100/bbl as carbon emission prices increase above 120/tonne CO2eq . In general, plants that co-fire lignite with biomass are less profitable (than 100% biomass plants) due to their higher net greenhouse gas emissions.